Inositol treatment of anovulation in women with polycystic ovary syndrome: a meta‐analysis of randomised trials. (14th July 2017) - Pundir, J; Psaroudakis, D; Savnur, P; Bhide, P; Sabatini, L; Teede, H; Coomarasamy, A; Thangaratinam, S
Abstract : Polycystic ovary syndrome is a common cause of anovulation and infertility, and a risk factor for development of metabolic syndrome and endometrial cancer. Systematic review and meta‐analysis of randomised controlled trials (RCT) that evaluated the effects of inositol as an ovulation induction agent. We searched MEDLINE, EMBASE, Cochrane and ISI conference proceedings, Register and Meta‐register for RCT and WHO trials' search portal. We included studies that compared inositol with placebo or other ovulation induction agents. Quality of studies was assessed for risk of bias. Results were pooled using random effects meta‐analysis and findings were reported as relative risk or standardised mean differences. We included ten randomised trials. A total of 362 women were on inositol (257 on myo‐inositol; 105 on di‐chiro‐inositol), 179 were on placebo and 60 were on metformin. Inositol was associated with significantly improved ovulation rate (RR 2.3; 95% CI 1.1–4.7; I 2 = 75%) and increased frequency of menstrual cycles (RR 6.8; 95% CI 2.8–16.6; I 2 = 0%) compared with placebo. One study reported on clinical pregnancy rate with inositol compared with placebo (RR 3.3; 95% CI 0.4–27.1), and one study compared with metformin (RR 1.5; 95% CI 0.7–3.1). No studies evaluated live birth and miscarriage rates. Inositol appears to regulate menstrual cycles, improve ovulation and induce metabolic changes in polycystic ovary syndrome; however, evidence is lacking for pregnancy, miscarriage or live birth. A further, well‐designed multicentre trial to address this issue to provide robust evidence of benefit is warranted. Tweetable abstract: Inositols improve menstrual cycles, ovulation and metabolic changes in polycystic ovary syndrome Tweetable abstract: Inositols improve menstrual cycles, ovulation and metabolic changes in polycystic ovary syndrome